Testing the MOND formula in the Galaxy - Famaey, B; Binney, J (2006)
The inner Galaxy is completely dominated by baryons, contrary to the predictions of CDM cosmology, whilst the observations are compatible with MOND if the local circular speed is smaller than 220 kms-1 and the asymptotic circular velocity close to 170 km s-1. © EAS, EDP Sciences 2006.